Computational Analysis of an Ammonia Combustion System for Future Two-Stroke Low-Speed Marine Engines - Jose R. Serrano; Ricardo Novella; Héctor Climent; Francisco José Arnau; Alejandro Calvo; Lauge Thorsen (Journal of Marine Science and Engineering)
Ammonia, being 17.6% hydrogen by mass, is regarded as a hydrogen carrier and carbon-free fuel as long as its production methods rely on renewable energy sources. The production and combustion of green ammonia do not generate carbon dioxide, offering a promising avenue for substantial reductions in greenhouse gas (GHG) emissions from a well-to-wake perspective. This paper presents a comprehensive methodology for the development and validation of a thermodynamic model for a two-stroke low-speed marine engine incorporating a hybrid ammonia-diesel diffusion combustion system. The simulation tools are rigorously validated using experimental data obtained during diesel operation. Subsequently, the study explores various aspects of the novel ammonia-diesel combustion system, addressing combustion and emissions characteristics. The investigation incorporates diverse simulation scenarios involving direct fuel injection through dedicated valves into the cylinder head of a six-cylinder, turbocharged compression-ignition engine. The engine features two diesel injection valves, employed to initiate the combustion process, and two ammonia injection valves. Simulation scenarios include variations in the injection timing of the pilot diesel injector and the relative orientation of diesel and ammonia sprays. Case C emerges as the preferred configuration, demonstrating superior metrics in terms of combustion stability, air-fuel mixing, and emissions profile compared to other cases. The results indicate a reduction of CO2 emissions of approximately 95% in mass compared to the baseline diesel operation. Furthermore, notable reductions in NOx emissions are observed, preliminarily attributed to the lower flame temperature of ammonia. Despite the appearance of N2O emissions as a result of ammonia oxidation, the overall potential reduction in GHG emissions, in CO2-equivalent terms, exceeds 85% at selected operating points. This work contributes valuable insights into the optimization of cleaner propulsion systems for maritime applications, facilitating the industry’s transition toward more sustainable and environmentally friendly practices.